Starożytna koncepcja trzech teologii - Chlewicka, Anna (Studia Europaea Gnesnensia, 2016)
The purpose of this article is to present the concept of three-fold theology (theologia tńpartite) combining mythical, civil and natural aspects, a theory abundantly discussed in Greek and Roman literature, spanning sources from the first century BCE (Plutarch, Ps.-Plutarch, Dio Chrysos-tom, Varro) to the Christian authors of the fourth and fifth centuries CE (Eusebius, Augustine, Tertullian). The paper also inquires into the origin of the theological trichotomy of theology, assessing those writings in terms of stoic influences, sińce stoicism is most likely the framework within which the theory first arose. Towards the end, the paper recounts how the three types of theology fiinctioned in the culture of Greece.